Synthesis and Optical Characterizations of the Fluorescence Silica Nanoparticles Containing Quantum Dots - Ha, Chu Viet; Anh Tuan, Chu; Thi Bich Ngoc, Nguyen; Nhung, Tran Hong; Liem, Nguyen Quang; Kim Lien, Vu Thi (VNU Journal of Science: Mathematics - Physics; Vol 36 No 2, 2020)
The quantum dots coated by silica  is fluorescence material class with great biocompatibility, low toxicity and water-solubility, that is suitable for bioapplications. This work presents the synthesis of SiO 2 coated CdTe/ZnSe (named CdTe) quantum dots (CdTe@SiO 2 nanoparticles) via a wet chemmical route called modified Stöber method. The compounds tetraethylorthosilicate (TEOS) has used as precursors, aminopropyltriethoxysilane (APTES) is  as  electric neutralizer, and ammonium hydroxide is used as catalysts. The size of CdTe@SiO 2 nanoparticles was estimated about 70 to 150 nm depending on the quantities of H 2 O, APTEOS, and catalysts. The emission behaviours of SiO 2 coated quantum dots was effected by ratio of substances participating in the reaction and synthesis conditions. with the ratio (by volume) of suitable substances: TEOS:solution of QDs:NH 4 OH:APTES:H 2 O being 1.5:1.5x10 -2 :0.8x10 -2 :4x10 -2 :3x10 -4 :5x10 -2 , the prepared silica nanoparticles containing quantum dots show high fluorescence emission efficiency, the fluorescence intensity is higher than that of uncoated CdTe/ZnSe quantum dots. This is a positive result in the technique of manufacturing luminescent silica nanoparticles containing quantum dots. The results show an ability to use the CdTe@SiO 2 nanoparticles for biological application.